Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon - Ott, Ricardo; Ruiz, Gustavo R.s.; Brescovit, Antonio D.; Bonaldo, Alexandre B. (Zootaxa, 2017)
The new genus Amazoonops is proposed for a group of species from the Brazilian Amazon that belong to the Varioonops group, which is presently composed by Varioonops Bolzern & Platnick, Ponsoonops Bolzern and Bipoonops Bolzern. In these genera, female lacks the dorsal abdominal scutum, have a reduced abdominal post-epigastric scutum, and the male palp has unfused cymbium and tegulum. The incomplete abdominal epigastric scutum of females and the sternal surface covered with deep pits in both sexes are considered as putative synapomorphies of the new genus. Five new species are described, four from the state of Pará (Amazoonops almeirim sp. nov., A. cachimbo sp. nov., A. caxiuana sp. nov. and A. juruti sp. nov.) and one from the state of Amazonas (A. ducke sp. nov.). Females of A. almeirim sp. nov. and A. ducke sp. nov. are unknown.